Better behavioral control in sharia investment decision: a literature review - Surendra Purusottama Rangga; Y Anni Aryani; Doddy Setiawan; Ibrahim Fatwa Wijaya; Setiyawan Gunardi (Universitas Islam Negeri Walisongo Semarang, 2025)
Purpose - This study aims to identify factors that influence investment decisions. Furthermore, the researcher wants to show how sharia-compliant investment decisions act more rationally than conventional investment decisions. Method - This study employs the